Fuzzy-Logic-Based Application to Combat Gender Violence - José Á. Concepción-Sánchez (International Journal of Computational Intelligence Systems, 2017)
Gender violence is one of the most serious and widespread problems in our society. In dangerous cases, the use of special devices for GPS tracing is recommended in some countries. However, these devices are used only in extreme cases and have many drawbacks. This work describes a new system to combat gender violence that tries to improve the existing system. It combines different location schemes based on distinct technologies to determine the distance between victim and aggressor. Besides, the application is enriched with a fuzzy-logic-based approach as a way to avoid false alarms. If an offender gets close to a victim, even if the established set distance has not been broken yet, the victim is warned thanks to the application. Moreover, if the fuzzy logic based approach confirms that the pre-set distance has been broken, an automatic streaming of a real-time video starts to be sent to the police, and some stored contacts are warned so that they can try to protect the victim until the police arrive. A beta-version has been implemented and the obtained results are promising.